Does mean systolic blood pressure less than 130 mm Hg ensure high rates of control to - Anthony Rodgers; Andrew Moran; Benjamin Martin; Brent Egan; Susan E Sutherland; Benjamin Riesser; Michael Rakotz (BMJ Open)
Objective The purpose of this study was to determine how strongly mean systolic blood pressure (mSBP, mm Hg) was related to hypertension control and if an mSBP<130 was required to achieve ≥80% control to <140/<90.Design mSBP and per cent control to <140/<90 at the last encounter were assessed in a cross-sectional analysis of two cohorts with hypertension: (1) randomised, controlled Systolic blood PRessure Intervention Trial (SPRINT) and (2) real-world American Medical Association’s Measure Accurately, Act Rapidly, Partner with patients Hypertension programme.Setting SPRINT randomised participants with hypertension to two SBP targets: <140 (standard treatment, SPRINT-S) and <120 (intensive treatment, SPRINT-I). MAP (Measure Accurately, Act Rapidly, Partner with patients) included adults with hypertension at five healthcare systems incentivised by payers to control BP to <140/<90.Participants SPRINT participants with year 2 data. Patients in MAP (had hypertension, were aged≥18 years, had ≥2 healthcare visits from November 2019 through October 2021 and received care from clinicians (n=544) with ≥24 patients.Primary and secondary outcome measures mSBP and control to <140/<90. In MAP, control to <140/<90 was assessed in clinicians grouped by 5 mm Hg increments in the mSBP of their patient panel.Results In SPRINT-S (n=4303) and SPRINT-I (n=4323), mSBP values at the last visit were 136.7 and 121.7 with BP<140/<90 in 61% and 88% of participants, respectively. In MAP, mSBP at the last visit (n=168 978 patients) was 132.1 with BP<140/<90 in 70% of participants. Among clinicians with participant mSBP of 120 to <125, 88% of their patients were controlled to <140/<90, similar to SPRINT-I. Control fell to 79% of patients, with clinician-level mSBP of 125 to <130, 71%, with mSBP of 130 to <135 and 57%, with mSBP of 135 to <140 (similar to SPRINT-S); mSBP accounted for 80% of variance in clinician-level hypertension control.Conclusions and relevance mSBP is strongly related to hypertension control. Moreover, mSBP<130 is required to attain control rates to <140/<90 in the range of 80% and higher.